Simulations to Assess the Performance of Multifactor Risk Scores for Predicting Myopia Prevalence in Children and Adolescents in China - Wang, Hong; Li, Liansheng; Wang, Wencan; Wang, Hao; Zhuang, Youyuan; Lu, Xiaoyan; Zhang, Guosi; Wang, Siyu; Lin, Peng; Chen, Chong; Bai, Yu; Chen, Qi; et al. (Frontiers in Genetics, 2022)
Background: Myopia is the most common visual impairment among Chinese children and adolescents. The purpose of this study is to explore key interventions for myopia prevalence, especially for early onset myopia and high myopia. Methods: Univariate and multivariate analyses were conducted to evaluate potential associations between risk factors exposure and myopia. LASSO was performed to prioritize the risk features, and the selected leading factors were used to establish the assembled simulation model. Finally, two forecasting models were constructed to predict the risk of myopia and high myopia. Results: Children with persistently incorrect posture had a high risk of myopia (OR 7.205, 95% CI 5.999–8.652), which was 2·8 times higher than that in students who always maintained correct posture. In the cohort with high myopia, sleep time less than 7 h per day (OR 9.789, 95% CI 6.865–13.958), incorrect sitting posture (OR 8.975, 95% CI 5.339–15.086), and siblings with SE < −6·00 D (OR 8.439, 95% CI 5.420–13.142) were the top three risk factors. Then, the integrated simulation models were established to prioritize multifactor and predict the prevalence of myopia, with AUCs of 0.8716 and 0.8167 for myopia and high myopia, respectively. Conclusion: The findings illustrate that keeping incorrect posture is the leading risk factor for myopia onset, while the onset age of myopia is the primary factor affecting high myopia progression. Age between 8 and 12 years is the crucial stage for clinical intervention, especially for children with parental myopia.